The history of sexuality - Foucault, Michel (Vintage Books, 1990)
Michel Foucult offers an iconoclastic exploration of why we feel compelled to continually analyze and discuss sex, and of the social and mental mechanisms of power that cause us to direct the questions of what we are to what our sexuality is.